Smart ultrafiltration membrane fouling control as desalination pretreatment of shale gas fracturing wastewater: The effects of backwash water. (September 2019) - Chang, Haiqing; Li, Tong; Liu, Baicang; Chen, Chen; He, Qiping; Crittenden, John C.
Abstract: Background: Increasing attention is being paid to the treatment of shale gas fracturing wastewater, including flowback and produced water (FPW). Energy-efficient pretreatment technologies suitable for desalinating and reusing FPW are of paramount importance. Objectives: This work focused on enhanced fouling alleviation of ultrafiltration (UF) as a pretreatment for desalinating shale gas FPW in Sichuan Basin, China. The UF fouling behaviors under various backwash water sources or coagulant dosages were evaluated, and membrane surface characteristics were correlated with UF fouling. The feasibility of Fourier transform infrared (FTIR) microscope mapping technique in quantifying UF fouling was also assessed. Methods: Various backwash water sources, including UF permeate, ultrapure water, nanofiltration (NF) permeate, reverse osmosis (RO) permeate, RO concentrate and forward osmosis (FO) draw solution, were used to clean UF membranes fouled by shale gas FPW. The UF fouling behaviors were characterized by total and non-backwashable fouling rates. Membrane surface characteristics were analyzed by scanning electron microscopy (SEM), total tension surface and FTIR spectra. Results: Protein-like substances in terms of fluorescence intensity in the backwash water decreased with the order of UF permeate, RO concentrate, NF permeate, RO permeate and FO draw solution. Compared with UF permeate backwashing, alleviated UF fouling was observed by using demineralized backwash water including ultrapure water and RO permeate, irrespective of hollow fiber and flat-sheet membranes. NF permeate and RO concentrate after NF used as backwash water resulted in low and comparable membrane fouling with that in integrated coagulation-UF process under optimal dosage. Among the backwash water tested, FO draw solution backwashing corresponded to the lowest UF fouling rates, which were even lower than that in the presence of coagulant under optimal dosage. The superiority of these backwash water sources to UF permeate was further confirmed by SEM images and FTIR spectra. The residual foulant mass on membrane surface and the total surface tension correlated well with non-backwashable and total fouling rates, respectively. Conclusions: FTIR microscopy was a powerful surface mapping technique to characterize UF membrane fouling caused by shale gas FPW. Backwash water sources significantly influenced the fouling of UF membranes. In the integrated UF-NF-RO or UF-FO process, RO concentrate or FO draw solution were proposed as backwash water to enhance UF fouling control and decrease waste discharge simultaneously. Graphical abstract: Unlabelled Image Highlights: Various backwash water sources are used to clean UF fouling by shale gas FPW. RO concentrate after NF outweighs UF permeate in backwashing FPW-fouled UF membrane. Backwashing with FO draw solution exhibits the best fouling control performance. Comparable UF fouling is obtained for backwash water adjustment and coagulation. FTIR mapping is a powerful surface characteristic technique to analyze UF fouling.